Phytogeographical origin of Madeiran common beans based on phaseolin patterns - Silva, Emanuel Marques da; Correia, Anísia Soraia Abreu; Lopes, Nuno Alexandre Amaral; Nóbrega, Humberto Gil Moreira; Ganança, José Filipe Teixeira; Domingues, Ana Maria; Khadem, Mahnaz; Slaski, Jan Jacek; Carvalho, Miguel Ângelo Almeida Pinheiro de (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to determine the geographic origin of the Madeiran common bean (Phaseolus vulgaris) gene pool. Phaseolin patterns of 50 accessions representing the diversity of common bean collected in Madeira, Portugal, and conserved in the ISOPlexis Germplasm Bank, were analysed using the Experion automated electrophoresis system, based on lab-on-a-chip technology. Five common bean standard varieties with typical phaseolin patterns were used to determine the phytogeographical origin of the Madeiran common bean accessions. Ninety two percent of the accessions exhibited a phaseolin pattern consistent with the one of common bean types belonging to the Andean gene pool, while the origin of the remaining 8% of the accessions was indistinguishable. The application of a similarity coefficient of 85%, based on Pearson correlations, increases the number of accessions with uncertain pattern. The analytical approach used permitted the determination of the origin of the common bean gene pool, which is Andean in 98% of the cases, and clustering of the observed variability among the Madeiran common beans.
Keywords: Phaseolus vulgaris; gene pool; genetic variability; germplasm; lab-on-a-chip technology